Notes on the Biology of the Green Tree Skink Lamprolepis smaragdina philippinica (Scincidae) in Siquijor Island, Philippines - Bucol, Abner A.; Alcala, Michael Lawton R.; Catid, Rosalina; Basa, Jocelyn Elise P.; Sequihod, Irish; Pagente, Albert; Kilat, Will (Silliman Journal, 2022)
Observations on the biology of the Green Tree Skink Lamprolepis smaragdina were conducted in Siquijor Island, Philippines. Morphological features such as body proportions, scale counts, and coloration of the population in Siquijor were contrasted with those from neighboring population on Negros Island. The population density of the species was also determined. Incidental observations on the foraging behavior are also presented.